Access and Equity in Greenspace Provision: A Comparison of Methods to Assess the Impacts of Greening Vacant Land2. Issue 6 (26th December 2012) - Heckert, Megan
Abstract This research explores three methods of measuring access to greenspace in Philadelphia and their implications for assessing equity in access based on race and socioeconomic status. These three methods are then used to assess the impacts of a vacant land greening program which turns vacant lots into temporary greenspaces. This research explores the differences between findings when access to greenspace is measured based on distance to any greenspace, total amount of greenspace to which residents have access, or a hybrid measure in which access is determined based on proximity to a threshold amount of greenspace. Not only do assessments of equity differ between the three approaches, but so do determinations of the impact of greening vacant land. Blacks, Hispanics and renters are more likely to live close to a public greenspace than whites or homeowners, but live in proximity to smaller overall amounts of greenspace. Greening vacant land increases the proportion of all residents who live within walking distance of a greenspace and lessens but does not eliminate differences in total greenspace access. The greatest effects of greening vacant land are seen in addressing differences in relative likelihood of having access to a threshold amount of greenspace.